Coupling of the Monte Carlo iMC and OpenFoam codes for multiphysics calculations of molten salt reactors - Kim, Inyup; Oh, Taesuk; Kim, Yonghee (Frontiers in Nuclear Engineering, 2025)
This paper presents the development of a multiphysics coupled framework of Monte Carlo neutronics iMC and OpenFOAM Computational Fluid Dynamics codes for molten salt reactor (MSR) analysis. The overall coupling scheme is handled, including the framework structure and iteration scheme. Also, related techniques to enhance the accuracy and efficiency of the coupling are introduced, such as delayed neutron precursor tracking. The framework is applied to a simple molten salt reactor model and achieves a converged solution. In addition, sensitivity studies on the neutronics mesh are performed. The research demonstrates the capability of the iMC-OpenFOAM coupled framework to achieve a converged solution and provides significant insights into the analysis of the MSRs.